Characterization of cellulase, hemicellulase and lipase and its use in deinking of laser printed paper - Lee Chee Keong; Darah Ibrahim; Ibrahim Che Omar (2013)
Aims: It is recognized that laser printed paper are difficult to deink using conventional method. This had lead to the suggestion of enzymatic approach to overcome the problem encountered by commonly employed deinking techniques. The present study aimed to investigate 7 commercially available enzymes for their suitability use in deinking of laser printed paper. Methodology and results: 3 cellulases, hemicellulases, xylanase and 2 lipases were used in enzymatic deinking of laser-printed wastepaper. Cellulase A “Amano”3 (C), Hemicellulase (H) and lipase (L) were selected for used in deinking because they possess either highest activity or broad pH stability compared to others enzymes. Different combination of enzymes was carried out to evaluate their effectiveness in deinking process. CH enzymes sequence was determined to be the most effective sequence in toner removal with 1.90% of brightness increment. However, only 0.95% of brightness increment was gained by enzyme sequence L. Highest deinking efficiency obtained was not proportional to the highest total reducing sugar produced. Conclusion, significance and impact of study: Enzyme (cellulase and hemicellulase) can be used to de-ink laserprinted wastepaper, which are difficult to be deinked by conventional chemical deinking process. Thus, enzyme deinking has high possibility as alternative method to current chemical deinking process which is not environmental friendly.